Calling out the COVID blues- how much of a psychological impact does the COVID-19 pandemic have on health care professionals in India - Halder, Arghya; Ghosh, Ambarish; Mondal, Nikhiles; Desai, Birva; Das, Priyanka; Maity, Satyabrata (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 pandemic is one of the rarest health crises the world has ever encountered. As mental health professionals; we need to consider the psychological impact of the pandemic. There are certain groups of people that are largely more vulnerable to pernicious effects on mental health including frontline healthcare workers. Hence, the current study was undertaken look into the minds of our covid warriors. Aims and Objectives: This study aims to assess psychological impact of COVID-19 pandemic among health care professionals, with the primary objectives being to study: 1. Perceived stress regarding COVID-19 pandemic among health care professionals. 2. Stigma associated with the pandemic, faced by health care professionals in their surroundings as well as in the society. 3. Obsessive-Compulsive symptoms among the health care professionals. The secondary objective of the study is to compare between High and Low exposure groups on the basis of different variables. Materials and Methods: This study is an observational, cross-sectional study wherein the sample size is 410, taken by consequent sampling. Data was collected from health care professionals all over India, by manual or digital interview. Health care professionals of a tertiary care hospital were taken up for the study including doctors, nurses and other hospital staff. Results: On K10 scale, 369 (90%) of the subjects had scores below 25, meaning they reported to have no or mild perceived stress, whereas 41 of them (10%) had scores 25 or above, meaning to have moderate or severe perceived stress. Forty (9.8%) subjects reported to be experiencing panic symptoms at the time of the interview. One hundred twenty-eight (31.2%) admitted to have faced stigma from the society in at least one of the facets of the questionnaire based on SARI stigma scale. 39 people (9.5%) reported to be experiencing OC symptoms at the time of interview. Conclusion: With this research we conclude that owing to the ongoing COVID-19 pandemic, the health care professionals are under a lot of stress, many of them have also experienced panic like symptoms. Large scale screenings should be carried out at regular intervals at hospitals to keep a check on the mental health of health care workers. Mental health should be given a priority by the government officials and sufficient awareness campaigns should be rolled out.